O kreacji bohatera pierwszoplanowego w słuchowisku satyrycznym - Maćkowiak, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The dynamic development and diversity of modern radio dramaturgy allows for deeper reflection on its generic varieties. Over time, the term “radio play” has become too broad, which is why it seems appropriate to differentiate between specific varieties. Without a doubt, satirical radio plays with all their specificity are worth paying closer attention to. An element of the narration worthy of particular attention is the main character, since he/she determines the overall narration: who influences other characters and whose goals and ambitions determine the plot and the story’s ending. Through the main character, the listener learns about the world of narration and about other characters who are placed within it. The text: “About the creation of the main character in the satirical radio drama” is an attempt to present a sketch of the problems connected with the creation of the protagonist in radio plays. The hypotheses put forward in the text are explained on the basis of radio plays that form part of a series entitled “Malinówek”, by Marek Ławrynowicz.